The Apocalyptic-lamenting worldview and the Idea of the restauration of the kingdom in 5th-12th c. Armenia(Some theoretical remarks) - Vardanyan, Areg (History and Culture, 2025)
The article introduces a novel conceptualization of political thinking in Medieval Armenia. In particular, the concepts of Apocalyptic-lamenting worldview and the Idea of the restauration of the kingdom are discussed. Apocalyptic-lamenting worldview denotes the mode of thinking that developed out of the complex interconnection between the medieval Armenian laments and apocalypses. This interconnection is clearly tracable on both textual, as well as, semantic levels. The way Medieval Armenian literature has evolved made this particular worldview an important paradigm for political reflection. The Idea of the restauration of the kingdom was initially a separate political idea that was effectively merged with Apocalyptic-lamenting worldview in the later Armenian written tradition.